2006
DOI: 10.1021/jm050850v
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fragment Screening and Fragment Linking to the Discovery of Novel Thrombin Inhibitors

Abstract: The screening of fragments is an alternative approach to high-throughput screening for the identification of leads for therapeutic targets. Fragment hits have been discovered using X-ray crystallographic screening of protein crystals of the serine protease enzyme thrombin. The fragment library was designed to avoid any well-precedented, strongly basic functionality. Screening hits included a novel ligand (3), which binds exclusively to the S2-S4 pocket, in addition to smaller fragments which bind to the S1 poc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 56 publications
1
93
0
2
Order By: Relevance
“…Thrombin has been under intense investigation for decades as a potential target for anticoagulation agents. Recent efforts have included fragment-based approaches using X-ray crystallography that led to the discovery of several fragment hits and the development of novel inhibitors (41). In particular, inhibitor 11 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thrombin has been under intense investigation for decades as a potential target for anticoagulation agents. Recent efforts have included fragment-based approaches using X-ray crystallography that led to the discovery of several fragment hits and the development of novel inhibitors (41). In particular, inhibitor 11 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Howard et al reported that during the course of their work to develop an inhibitor of the protease enzyme thrombin, linking two optimally bound fragments together compromised the original fragment orientations. [16] Huth et al failed to observe the desired increase in potency upon linking of two HSP90-binding fragments, potentially due to a suboptimal linker strategy, which introduced an unfavorable energy penalty. [17] Both the length and the chemical nature of the linker influence fragment binding.…”
Section: Fragment Optimisation: Linking and Growingmentioning
confidence: 99%
“…В результаті бу-ло синтезовано ряд сполук, IC 50 найактивнішої се-ред яких становило 1,4 нM (рис. 7б) [54]. Хоча й є успішні приклади методу з'єднання фрагментів, вони залишаються швидше винятками.…”
Section: переваги та недоліки фрагмент-орієнто-ваного дизайну лікарсьunclassified